Imaging of Bronchial Pathology in Antibody Deficiency: Data from the European Chest CT Group - Schütz, Katharina; Alecsandru, Diana; Grimbacher, Bodo; Haddock, Jamanda; Bruining, Annemarie; Driessen, Gertjan; de Vries, Esther; van Hagen, Peter M; Hartmann, Ieneke; Fraioli, Francesco; Milito, Cinzia; Mitrevski, Milica; et al. (Journal of clinical immunology, 2019)
Studies of chest computed tomography (CT) in patients with primary antibody deficiency syndromes (ADS) suggest a broad range of bronchial pathology. However, there are as yet no multicentre studies to assess the variety of bronchial pathology in this patient group. One of the underlying reasons is the lack of a consensus methodology, a prerequisite to jointly document chest CT findings. We aimed to establish an international platform for the evaluation of bronchial pathology as assessed by chest CT and to describe the range of bronchial pathologies in patients with antibody deficiency. Ffteen immunodeficiency centres from 9 countries evaluated chest CT scans of patients with ADS using a predefined list of potential findings including an extent score for bronchiectasis. Data of 282 patients with ADS were collected. Patients with common variable immunodeficiency disorders (CVID) comprised the largest subgroup (232 patients, 82.3%). Eighty percent of CVID patients had radiological evidence of bronchial pathology including bronchiectasis in 61%, bronchial wall thickening in 44% and mucus plugging in 29%. Bronchiectasis was detected in 44% of CVID patients aged less than 20 years. Cough was a better predictor for bronchiectasis than spirometry values. Delay of diagnosis as well as duration of disease correlated positively with presence of bronchiectasis. The use of consensus diagnostic criteria and a pre-defined list of bronchial pathologies allows for comparison of chest CT data in multicentre studies. Our data suggest a high prevalence of bronchial pathology in CVID due to late diagnosis or duration of disease.
Keywords: běžná variabilní imunodeficience; Male; Common Variable Immunodeficiency; Infant; předškolní dítě; Chest CT; CVID; Bronchiectasis; bronchial pathology; Child, Preschool; Humans; bronchiektazie; syndromy imunologické nedostatečnosti; počítačová rentgenová tomografie; Tomography, X-Ray Computed; senioři; mužské pohlaví; Female; Bronchi; mladiství; Aged; spirometrie; hrudní stěna; ženské pohlaví; kojenec; mladý dospělý; Adult; Young Adult; Thoracic Wall; bronchiectasis; primary antibody deficiency; Spirometry; Adolescent; Immunologic Deficiency Syndromes; dospělí; dítě; bronchy; lidé; Child